Financialisation in currency, energy and residential property markets - Trevor Evans; Hansjörg Herr (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2016)
The markets for foreign exchange, energy and residential housing have all been strongly affected by the deregulation and expansion of the financial sector. As a result, they have begun to follow the logic of asset markets. This was especially marked in the case of the foreign exchange market from the 1970s, but has also been the case to some extent for residential housing markets since the mid-1990s, and more strongly for energy markets since the early 2000s. Deregulation has led to far greater price volatility and the rise of unsustainable price and credit bubbles which, when they burst, can pose a significant threat to financial and economic stability. For this reason, these markets should be subjected to new and appropriate forms of regulation.
Keywords: E32; E44; E65; G18; G21; G28; 330; asset bubbles; financial crises; foreign exchange rates; energy prices; house prices